O papel do pedagogo no espaço de acolhimento para crianças e adolescentes - EACA em Abaetetuba-PA - SANTOS, Suellen Cardoso dos (2022)
The research's object of study is to reflect on the role of the pedagogue in institutions for children and adolescents. These institutions that serve children and adolescents are part of the High Complexity Service of the Unified Social Assistance System (SUAS) as a legal measure of protection guaranteed by the Statute of Children and Adolescents. It is important to emphasize that, in order to reach these spaces, the children have already gone through atypical cases of family coexistence, so it is necessary to have in the institution a team of professionals from various areas to better serve them, including a pedagogue, since that pedagogy encompasses all forms of education that occurs inside and outside the school, where the Law of Directives and Bases of National Education defines that the education process is formatted in several segments, among them, in the family, in the coexistence in society , work and culture. In view of this, pedagogy is concerned with educating, taking into account a human perspective, theories and educational methods. In this case, complementing in an interrelated way the team of professionals in these spaces. The research is qualitative, where the bibliographic research was also present. The data collection technique was carried out through interviews. The results indicate that the pedagogy professional plays an important role in the dynamics of the institution, not only because of their pedagogical didactic training, but also because of the humanistic nature of the profession itself.